'If p? Then What?' Thinking within, with, and from cases. (October 2020) - Morgan, Mary S.
The provocative paper by John Forrester 'If p, Then What? Thinking in Cases' (1996) opened up the question of case thinking as a separate mode of reasoning in the sciences. Case-based reasoning is certainly endemic across a number of sciences, but it has looked different according to where it has been found. This article investigates this mode of science – namely thinking in cases – by questioning the different interpretations of 'If p ?' and exploring the different interpretative responses of what follows in 'Then What?'. The aim is to characterize how 'reasoning in, within, with, and from cases' forms a mode of scientific investigation for single cases, for runs of cases, and for comparative cases, drawing on materials from a range of different fields in which case-based reasoning appears.